The dynamics of natural satellites of the planets - Emelyanov, Nikolay (Elsevier, 2020)
The Dynamics of Natural Satellites of the Planets is an accessible reference for understanding the celestial mechanics of planetary moons through the lens of both theory and observation. Based on decades of research by the author, the book utilizes state-of-the-art observations of the natural satellites in the solar system to establish models, measurements and calculations to better understand the theory of the satellite movement and dynamics. It presents an extensive set of study methods and results on the motion of natural satellites of the planets and includes reviews and references to related publication for further explanation. By relating observations to numerical theory, the book serves as a quick and comprehensive reference for applying the theory of orbital dynamics to observational data on orbits and physical properties of the natural satellites in order to formulate state-of-the-art explanations and models, particularly for determining the parameters of satellite motion.